2002
DOI: 10.1348/000712602761381330
|View full text |Cite
|
Sign up to set email alerts
|

Judgments under uncertainty: Representativeness or potential surprise?

Abstract: Tversky and Kahneman's (1983) account of conjunctive probability judgment in terms of the representativeness heuristic is questioned. Instead, potential surprise (Shackle, 1969) is proposed as an important mechanism underlying subjective probability judgment. Study 1 reveals that, consistent with Shackle's theory, probabilities assigned to conjunctions are predominantly determined by the magnitude of the smaller component event probability. Also consistent with Shackle, Study 2 shows that for disjunctions, thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
63
0
4

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(78 citation statements)
references
References 21 publications
(45 reference statements)
7
63
0
4
Order By: Relevance
“…This is because the disjunctive probability equals one minus the probability of the conjunction B and F , and the latter is predicted to produce a conjunction error because of incompatibility. Indeed, it has been found that disjunction errors are also obtained using the same events that produce conjunction errors (Morier & Borgida, 1984;Fisk, 2002;Yates & Carlson, 1986). Furthermore, another directly testable prediction of the QP model concerns conditional probabilities: The QP model must predict that p(B|F, L) ≥ p(B|L), because the QP model for the conjunction fallacy implies that B|F, L).…”
Section: Concluding Commentsmentioning
confidence: 99%
“…This is because the disjunctive probability equals one minus the probability of the conjunction B and F , and the latter is predicted to produce a conjunction error because of incompatibility. Indeed, it has been found that disjunction errors are also obtained using the same events that produce conjunction errors (Morier & Borgida, 1984;Fisk, 2002;Yates & Carlson, 1986). Furthermore, another directly testable prediction of the QP model concerns conditional probabilities: The QP model must predict that p(B|F, L) ≥ p(B|L), because the QP model for the conjunction fallacy implies that B|F, L).…”
Section: Concluding Commentsmentioning
confidence: 99%
“…Ekman, 1972;Fisk, 2002;Izard, 1977;Plutchik, 1980;Roseman, 1996) which usually results in the interruption of ongoing thoughts and activities and motivates people to pay attention to the unexpected (e.g., Kunda et al, 1990;Meyer, Reisenzein, & Schützwohl, 1997;Ortony & Partridge, 1987;Schützwohl & Reisenzein, 1999). Distinct from emotions such as joy or fear, surprise does not presuppose the appraisal of the eliciting information as positive (motive-congruent) or negative (motive-incongruent), and the feeling of surprise is per se hedonically neutral rather than pleasant or unpleasant (Reisenzein, 2009).…”
Section: The Emotional Experience Of Surprisementioning
confidence: 99%
“…Some psychologists treat surprise as a cognitive process that involves beliefs about the likelihood of an event (Fiske 2002;Teigen and Keren 2003). Others view surprise as an emotion, on par with happiness, sadness, anger, disgust, and fear, because of its unique pattern of facial expressions (Ekman, Friesen and Ellsworth 1972).…”
mentioning
confidence: 99%